2018
DOI: 10.1111/cge.13245
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory network analysis of LINC00472, a long noncoding RNA downregulated by DNA hypermethylation in colorectal cancer

Abstract: Colorectal cancer (CRC), one of the common malignant cancers in the world, is caused by accumulated alterations of genetic and epigenetic factors over a long period of time. Along with that protein-coding genes being identified as oncogenes or tumor suppressors in CRC, a number of lncRNAs have also been found to be associated with CRC. Considering the important regulatory role of lncRNAs, the first goal of this study was to identify CRC-associated lncRNAs from a public database. One such lncRNA, LINC00472, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…In the present study, we found that Linc00472 expression was decreased in CRC tissues, further verified by TCGA cohort. In parallel with our study, two latest publications also revealed low Linc00472 expression presented in CRC [ 15 , 24 ]. Our study further demonstrated that Linc00472 suppressed proliferation and induced apoptosis in CRC cells.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we found that Linc00472 expression was decreased in CRC tissues, further verified by TCGA cohort. In parallel with our study, two latest publications also revealed low Linc00472 expression presented in CRC [ 15 , 24 ]. Our study further demonstrated that Linc00472 suppressed proliferation and induced apoptosis in CRC cells.…”
Section: Discussionsupporting
confidence: 90%
“…Increasingly research indicated the effect of lncRNAs on various diseases, including lung cancers [8]. linc00472 expression was associated with less aggressive cancer and more favorable disease outcomes of breast cancer [9] and colorectal cancer [10]. However, until now, the role and molecular mechanism of linc00472 in the LC development are still not clarified yet.…”
mentioning
confidence: 99%
“…Therefore, we extracted 1 step of neighbor nodes of 2 networks with degree of nodes greater than 20 and maintained the original connection. These nodes that participate in multiple connections in the network are defined as markers such as oncogene PVT1 [ 20 , 21 ], LINC00472 [ 22 ], multiple tumor suppressor CDKN2A [ 23 ], prognostic Biomarkers in NSCLC FAM83B [ 24 ], cancer susceptibility gene BRCA2 in LUSC and HOXA11-AS [ 25 ], HNF1A-AS1 [ 26 ], LINC00511 [ 27 , 28 ], and HOTAIR [ 29 32 ] in LUAD ( Figure 4A, 4B ). There are many genes in this network that are significantly associated with survival of patients with 2 types of cancer ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%